Climate Change Impact on the Hydrology of a Typical Watershed in the Tianshan Mountains. (15th November 2015) - Fang, Gonghuan; Yang, Jing; Chen, Yaning; Zhang, Shuhua; Deng, Haijun; Liu, Haimeng; De Maeyer, Philippe
Abstract : To study the impact of future climatic changes on hydrology in the Kaidu River Basin in the Tianshan Mountains, two sets of future climatic data were used to force a well-calibrated hydrologic model: one is bias-corrected regional climate model (RCM) outputs for RCP4.5 and RCP8.5 future emission scenarios, and the other is simple climate change (SCC) with absolute temperature change of −1 6°C and relative precipitation change of −20% 60%. Results show the following: (1) temperature is likely to increase by 2.2°C and 4.6°C by the end of the 21st century under RCP4.5 and RCP8.5, respectively, while precipitation will increase by 2% 24%, with a significant rise in the dry season and small change in the wet season; (2) flow will change by −1% 20%, while evapotranspiration will increase by 2% 24%; (3) flow increases almost linearly with precipitation, while its response to temperature depends on the magnitude of temperature change and flow decrease is significant when temperature increase is greater than 2°C; (4) similar results were obtained for simulations with RCM outputs and with SCC for mild climate change conditions, while results were significantly different for intense climate change conditions.